A Model for Academics' Perceptions of Organizational Structure,Individual Performance and Turnover Intention - Zincirli, Muhammed; Turhan, Muhammed (My University, 2021)
The study aims to develop a model for the relationship between the current organizational structure, along with some variables, in universities, which are an educational organization, and the perceptions of academics' individual performance and turnover intention. While the population of research is composed of all universities carrying out educational activities in Turkey, the sample of research consists of a total of 37 universities selected by quota sampling method by taking into account certain criteria. Analyses were performed on the data obtained from a total of 1242 academics working at these universities. Following the analyses, it was determined that there was a positive interaction between the enabling organizational structure and the academics' perceptions of individual performance and other positive variables, and that a positive interaction existed between the coercive organizational structure and the academics' perceptions of the turnover intention and other negative variables. Moreover, it was found that the positive relationship of the coercive organizational structure with the turnover intention and other negative variables was stronger than the negative relationship of the enabling organizational structure. Based on these results, it was concluded that it is necessary, but not sufficient, to have an enabling organizational structure in order to increase the positive feelings, attitudes and behaviours of academics.
Keywords: Eğitim; Eğitim Araştırmaları; Kamu Yönetimi